Medicinal Plant of Madhya Pradesh Analysing Phytochemical and Their Role in Antibacterial Activity (International Journal of Food and Nutritional Sciences, 2023)
Medicinal plants of Madhya Pradesh, a state rich in biodiversity, have long been used in traditional healthcare systems for their therapeutic properties. This study focuses on the phytochemical analysis of selected medicinal plants native to Madhya Pradesh and their antibacterial activity. Various plants, including Azadirachta indica (Neem), Ocimum sanctum (Tulsi), Terminalia chebula (Haritaki), and Withania somnifera (Ashwagandha), were selected for their known medicinal benefits.